The Serum Level of Vascular Endothelial Growth Factor (VEGF) is Declined after Paclitaxel-Carboplatin Combined Chemotherapy Treatment on Epithelial Ovarian Cancer - Amelia Abdullah (Indonesian Journal of Obstetrics and Gynecology, 2012)
Objective: To assess the effect of Paclitaxel-Carboplatin combination on epithelial ovarian cancer by studying the changes in VEGF serum levels after receiving 3 series of chemotherapy. Methods: This was a cohort study conducted at several teaching hospitals in Obstetrics and Gynecology Department of the Faculty of Medicine, Hasanuddin University from April 2011 to March 2012. The subjects were patients with ovarian cancer who met the inclusion criteria and had undergone surgery. The clinical staging was determined with 2009 FIGO criteria. They went through histopathology examination to determine the histological type and cell differentiation of the lesion. They also went through combined chemotherapy of Paclitaxel and Carboplatin. The data were analyzed with paired t-test. Results: The study reveals that out of 30 cases of ovarian cancer who received a combination chemotherapy, most were < 45 years of age (53.33%), nulliparous (46.7%), serosum type (53.3%), with moderate differentiation (36.7%), and in advanced stage (73.3%). The VEGF serum level after 3 series of chemotherapy was lower than before (the average value: 294.67 vs 572.77 ng/ml). There was a significant change in VEGF serum level after receiving chemotherapy (p=0.000). The VEGF serum level of advanced-stage and early stage epithelial ovarian cancer after chemotherapy decreases significantly (p=0.000 and p=0.011). The advanced-stage cases showed more responses to chemotherapy than the early-stage did. There was a tendency that adenocarcinoma serosum type was more responsive to the therapy than mucinosum type (p=0.000 vs 0.003). Conclusion: There is no difference in VEGF serum level based on cell differentiation but there is a tendency that well and moderate differentiated cells have a greater change than the poor differentiated cells (p=0.003, p=0.003 vs p=0.019). [Indones J Obstet Gynecol 2012; 36-3: 135-9] Keywords: carboplatin, epithelial ovarian cancer, paclitaxel, VEGF